Comparison between commercial pellets and golden apple snail pellets as food for Tilapia nilotica fingerlings. - Arboleda, Daphne
The viability of Golden apple snail food for Tilapia nilotica was determined by comparing it with commercial pellets. The experiment was conducted on February 3, 1997. The two treatments had three replicates each with a stocking density of 15 fingerlings each. Comparison of growth curves showed that fingerlings fed with commercial pellets grew significantly (P<0.01) faster than those fed with golden apple snail pellets. The computed FCR was also greater for commercial pellets., The results suggest that golden apple snail alone does not promote efficient growth in Tilapia nilotica fingerlings. Thus it is recommended that golden apple snail be combined with other food ingredients to enable its efficient utilization as protein source.